Efektifitas Sistem Informasi Administrasi Kependudukan (SIAK) pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bondowoso - Dini Noor Aini; Alfian Firmansyah (Majalah Ilmiah DIAN ILMU, 2022)
The purpose of the study was to determine the effectiveness of the Population Administration Information System (Sistem Informasi Administrasi Kependudukan/SIAK) covering human resources, population data, facilities and infrastructure at the Population and Civil Registration Office of Bondowoso Regency. Research with a qualitative approach uses informants from the Population and Civil Registration Office of Bondowoso Regency and the use of SIAK services. Data collection techniques are through interviews, observations, and documentation which are then carried out by data reduction, data presentation, and drawing conclusions. The effectiveness of the population administration information system at the Population and Civil Registration Office of Bondowoso Regency has been implemented quite effectively, even though all SIAK management operators are contract workers.